2009
DOI: 10.1016/j.neuron.2009.09.005
|View full text |Cite|
|
Sign up to set email alerts
|

Representations of Odor in the Piriform Cortex

Abstract: Olfactory perception is initiated by the recognition of odorants by a large repertoire of receptors in the sensory epithelium. A dispersed pattern of neural activity in the nose is converted into a segregated map in the olfactory bulb. How is this representation transformed at the next processing center for olfactory information, the piriform cortex? Optical imaging of odorant responses in the cortex reveals that the piriform discards spatial segregation as well as chemotopy and returns to a highly distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

54
443
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 538 publications
(530 citation statements)
references
References 51 publications
(76 reference statements)
54
443
1
Order By: Relevance
“…Recent anatomical studies in mice showed that axons from identified glomeruli project diffusely throughout the piriform cortex [6][7][8][9] , the largest target area of the OB, and that piriform neurons receive convergent inputs from multiple mitral cells distributed throughout the OB 10 . These findings are consistent with an optical imaging study that found no apparent spatial organization of odour-evoked activity patterns in the piriform cortex 11 . In contrast, the anterior olfactory nucleus and the cortical amygdala receive topographic and biased projections from the OB, respectively 9,10 .…”
supporting
confidence: 91%
“…Recent anatomical studies in mice showed that axons from identified glomeruli project diffusely throughout the piriform cortex [6][7][8][9] , the largest target area of the OB, and that piriform neurons receive convergent inputs from multiple mitral cells distributed throughout the OB 10 . These findings are consistent with an optical imaging study that found no apparent spatial organization of odour-evoked activity patterns in the piriform cortex 11 . In contrast, the anterior olfactory nucleus and the cortical amygdala receive topographic and biased projections from the OB, respectively 9,10 .…”
supporting
confidence: 91%
“…For example, humans are very poor at identifying components in a mixture, even when they are familiar with the components alone (5-7). Similarly, cortical patterns of neural activity induced by a mixture are unique, not a combination of neural activities induced by the mixtures' components (25)(26)(27)(28)(29). Moreover, the pattern of neural activity in the olfactory bulb induced by the smell of a natural object typically reflects the pattern associated with the dominant monomolecular odorant (alone) associated with that object (30).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that a similar organizational logic may be operative in mammals, where information from the olfactory bulb bifurcates to project to limbic structures and the piriform cortex. Stereotyped connections to the amygdala may mediate innate olfactory responses and random inputs to the piriform cortex (38) may mediate more measured or learned olfactory behavior.…”
Section: Discussionmentioning
confidence: 99%